Impact of Green HRM Practices on Environmental Performance: The Mediating Role of Green Innovation - Kuo, Yen-Ku; Khan, Tariq Iqbal; Islam, Shuja Ul; Abdullah, Fakhrul Zaman; Pradana, Mahir; Kaewsaeng-on, Rudsada (Frontiers in Psychology, 2022)
Numerous organizations have faced substantial environmental performance challenges resulting from more than a half-century of worldwide industrialization. Grounded in social learning theory and Recourse-Based view theory, this study explores environmental performance and its impact on employees and industry outcomes. Drawing on a cross-sectional online survey of 500 full-time employees working in the chemical industry in Lahore, Pakistan. The results revealed a significant positive influence of Green HRM practices on employees’ Green innovation as well as on environmental performance. Additionally, significant influences of study variables were recorded on outcomes such as green compensation and reward, green performance management and appraisal, green training and development, and green recruitment and selection. Several key policy insights and future research directions are suggested, along with theoretical and practical implications.